Preserved Left Ventricular Function despite Myocardial Fibrosis and Myopathy in the Dystrophin-Deficient D2.B10-Dmdmdx/J Mouse. (16th March 2022) - Hayes, Holly M.; Angerosa, Julie; Piers, Adam T.; White, Jason D.; Koleff, Jane; Thurgood, Madeline; Moody, Jessica; Cheung, Michael M.; Pepe, Salvatore
Abstract : Duchenne muscular dystrophy involves an absence of dystrophin, a cytoskeletal protein which supports cell structural integrity and scaffolding for signalling molecules in myocytes. Affected individuals experience progressive muscle degeneration that leads to irreversible loss of ambulation and respiratory diaphragm function. Although clinical management has greatly advanced, heart failure due to myocardial cell loss and fibrosis remains the major cause of death. We examined cardiac morphology and function in D2.B10-Dmd mdx /J (D2- mdx ) mice, a relatively new mouse model of muscular dystrophy, which we compared to their wild-type background DBA/2J mice (DBA/2). We also tested whether drug treatment with a specific blocker of mitochondrial permeability transition pore opening (Debio-025), or ACE inhibition (Perindopril), had any effect on dystrophy-related cardiomyopathy. D2- mdx mice were treated for six weeks with Vehicle control, Debio-025 (20 mg/kg/day), Perindopril (2 mg/kg/day), or a combination (n = 8 /group). At 18 weeks, compared to DBA/2, D2- mdx hearts displayed greater ventricular collagen, lower cell density, greater cell diameter, and greater protein expression levels of IL-6, TLR4, BAX/Bcl2, caspase-3, PGC-1 α, and notably monoamine oxidases A and B. Remarkably, these adaptations in D2- mdx mice were associated with preserved resting left ventricular function similar to DBA/2 mice. Compared to vehicle, although Perindopril partly attenuated the increase in heart weight and collagen at 18 weeks, the drug treatments had no marked impact on dystrophic cardiomyopathy.